Expression of an Mg2+-Dependent Hiv-1 Rnase H Construct for Drug Screening - Valenzuela-Montenegro, B (2011)
A single polypeptide of the HIV-1 reverse transcriptase that reconstituted Mg2+-dependent RNase H activity has been made. Using molecular modeling, the construct was designed to encode the p51 subunit joined by a linker to the thumb (T), connection (C), and RNase H (R) domains of p66. This p51-G-TCR construct was purified from the soluble fraction of an Escherichia coli strain, MIC2067(DE3), lacking endogenous RNase HI and HII. The p51-G-TCR RNase H construct displayed Mg2+-dependent activity using a fluorescent nonspecific assay and showed the same cleavage pattern as HIV-1 reverse transcriptase (RT) on substrates that mimic the tRNA removal required for second-strand transfer reactions. The mutant E706Q (E478Q in RT) was purified under similar conditions and was not active. The RNase H of the p51-G-TCR RNase H construct and wild type HIV-1 RT had similar Kms for an RNA-DNA hybrid substrate and showed similar inhibition kinetics to two known inhibitors of the HIV-1 RT RNase H. Copyright © 2011, American Society for Microbiology. All Rights Reserved.